Pengukuran Kinerja Perusahaan Menggunakan Metode Performance Prism (Studi Kasus di Cendana Offset Fokus Intermedia Grup) - Anissa Rianda Putri; Azmi Mas’ud; Selvia Mayangsari; Yuniaristanto - (Performa: Media Ilmiah Teknik Industri, 2016)
This article explain about a performance measurement research in a graphic arts industry using Performance Prism method. The previous performance measurement system in that company has not been able to represent the performance of the organization. The performance prism method is used because this method complete the exiting methods. The stakeholder in CV. Cendana Offset consists of customers, investors or owners, communities, governments, employees, and suppliers. The company’s system contains 10 KPI performance with 2 KPI of customers, 2 KPI of employees, 2 KPI of investor/owner, 2 KPI of suppliers, and 2 KPI of government. Based on the result, there is the fundamental problems in special services for customers. Based on the problem that have been discovered, this article propose several option for improvement. One of them is by providing great discounts on certain periods and improving the print quality through increasing the company resources (i.e. operator’s skill and production machines).